The authority of the Federal Court of Cassation to alter the legal adaptation of the crime - Maan, Mays; Saadoon, Samer (Journal of Legal Sciences, 2022)
The Federal Court of Cassation is a court of law that monitors the lower courts through its scrutiny of the judgments and decisions issued by these courts, and that its oversight is focused on the legal side of the penal ruling, as it monitors the extent to which the subject courts adhere to the correct application of the rules of substantive and formal law represented in the process of legal adjustment. The Federal Court of Cassation has control over legal adaptation, as it is one of the legal issues, and therefore it has the power to change the adjustment with ratification of the penalty or reducing it according to certain controls in which its authority is determined.